A Nordic model for learning compassionate care in clinical education - Hilli, Yvonne; Sandvik, Ann-Helén (Nurse Education Today, 2020)
Background Preceptorship is one model of supporting student nurses' learning and development during their clinical education. However, little is known about what there is in preceptorship that promotes or hinders learning. Earlier studies found that there were ethical dimensions to students' encounters with preceptors. Aim The overall purpose of this Nordic follow-up study was to develop a model for learning compassionate care among student nurses during their clinical education - first, to deeper understand the learning of student nurses, and second, to investigate the phenomenon of preceptorship from the preceptors´ point of view. Method This study used a mixed methods design. Undergraduate student nurses (n = 139) from three universities in Finland and Sweden were shadowed for a period of three years. Quantitative data were collected through a questionnaire and were analysed using statistical methods. To better understand the learning acquired by the student nurses, focus group interviews (n = 70) were conducted. The phenomenological-hermeneutical approach was adopted. To capture the preceptors' point of view, narrative interviews were held with them (n = 88) in western Finland and northern Sweden. A hermeneutical approach was used when analysing the data. Findings According to both student nurses and preceptors, a caring student-preceptor relationship, imbued with commitment, reverence and responsibility, is fundamental and serves as the basis for students' learning and development more than pedagogical methods used. Three main themes emerged: a caring student-preceptor relationship; a caring manner of being—the conduct; and a caring culture—the tone of the learning space. Conclusions This study shows the importance of preceptorship on student nurses in their quest of becoming compassionate and caring nurses. Therefore, based on earlier findings and the findings in this study, there is a need to facilitate and support the students' transformation, that is, the process of becoming, from student to a ...